Sex and APOE genotype modulate neuropsychological profile and depression in temporal lobe epilepsy - Bruno, Francesco; Spadafora, Patrizia; Veltri, Ida; Cuconati, Mario L.; Condino, Francesca; Cerantonio, Annamaria; De Benedittis, Selene; Greco, Beatrice M.; Di Palma, Gemma; Gallo, Olivier; Citrigno, Luigi; Qualtieri, Antonio; et al. (Frontiers in Neuroscience, 2025)
IntroductionTemporal lobe epilepsy is the most common form of focal epilepsy, often associated with cognitive impairments, particularly in memory functions, and depression. Sex and APOE ε4 genotype play a crucial role in modulating cognitive outcomes and depression in various neurological conditions like Alzheimer's disease. However, the combined effects of APOE genotype and sex on cognitive performance and depression in temporal lobe epilepsy have not been previously investigated.ObjectiveThis study aims to (i) identify impaired cognitive performance and clinically relevant depression; (ii) explore the interaction between sex and APOE ε4 genotype on cognitive performance and depression in individuals with temporal lobe epilepsy.MethodsWe used a comprehensive battery of neuropsychological tests to assess domains such as learning and memory, attention, executive functions, language, and visuo-spatial constructional skills and the Hamilton Depression Rating Scale. We also performed APOE genotyping to assess its role in the study. The final sample was composed by fifty-four patients (53.7% female). Cognitive performance and depression were analyzed using normative cut-off scores. To examine the main effects and interactions of sex and APOE ε4 carrier status on neuropsychological test scores and the Hamilton Depression Rating Scale, we also conducted a two-way Analysis of Variance (ANOVA).ResultsFemale APOE ε4 carriers compared to normative cut-offs, exhibited poor performance on multiple test scores, including the MMSE, The Rey Auditory Verbal Learning Test (immediate and delayed recall), The Corsi Block-Tapping Task, The Verbal Fluency Test, The Raven's Standard Progressive Matrices and The Pentagon-copying Test. Males showed impairment only in visuo-spatial short-term memory. ANOVA analysis revealed significant main effects of APOE ε4 status and sex on the MMSE, The Rey Auditory Verbal Learning Test, The Verbal Fluency, The Raven's Standard Progressive Matrices and The Pentagon-copying Test scores. Specifically, female APOE ε4 carriers performed consistently worse than other groups on many tasks. For depression, only an effect of sex emerged. Females scored higher besides APOE genotype.ConclusionsThese findings underscore the importance of considering both sex and APOE genotype when assessing cognitive performance in patients with temporal lobe epilepsy. The significant cognitive deficits we observed among females carrying the APOE ε4 allele highlight previously unexplored genetic and sex-related influences on cognition. This has potential implications for personalized therapeutic strategies, emphasizing the need for targeted assessment and intervention.